Contribution Of Srimanta Sankardeva's Neo- Vaishnavism To The Indian Education System (Journal of Namibian Studies : History Politics Culture, 2023)
In Indian history, Mahapurush Srimanta Sankardeva occupies a very special place. He was one of the greatest saints of Mediaeval period in Mahapurush Srimanta Sankardeva had a crucial role in history of man kind. He is widely credited with building on past cultural relics and devising new forms of music( Borgeet), theatrical performance (Ankia Naat,Buaona),dance ( Satriya) , literacy language (Brajawali). Besides,he has left an extensive literary oeuvre of trans- created scriptures ( Bhagavat of Sankardeva) and different theological works. The Bhagavatic religious movement he started,Ekasarana Dharma which also called as Neo- Vaishnavite movement, influenced two of the mediaeval kingdoms - the Koch Kingdom and Ahom Kingdom and the assembly of devotees he initiated evolved over time into monastic centres called Sattras,which continue to be important social- religious institutions in Assam just as Guru Nanak,Ramananda,Kabir ,Basava and Chaitanya Mahaprabhu inspired it elsewhere in the Indian subcontinent. His influence spread even to some kingdoms as the Matak Kingdom founded by Bharat Singha and consolidated by Sarbananda Singha in the later 18th century endorsed his teachings.